2010
DOI: 10.1186/1755-1536-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid P ameliorates radiation-induced oral mucositis and fibrosis

Abstract: PurposeTo evaluate the effect of the anti-fibrotic protein serum amyloid P (SAP) on radiation-induced oral mucositis (OM) and fibrosis in a hamster cheek-pouch model.Experimental DesignHamsters received a single dose of radiation (40 Gy) to the left everted cheek pouch to induce significant OM. The protective therapeutic potential of SAP was evaluated using varying dosing regimens. The extent of OM was measured using a validated six-point scoring scheme ranging from 0 (normal tissue, no mucositis) to 5 (comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…SAP is a pattern recognition protein that binds components of pathogens as well as apoptotic and autoimmune material [12,13]. SAP is involved in wound repair and the innate immune response [1416], and is a potent regulator of monocyte responses controlling fibrosis [1721]; however, SAP also potentially contributes to the pathogenesis of Alzheimer’s disease through the binding of amyloid plaques and neurofibrillary tangles (NFTs) [22–24]. SAP has been found to enter neurons, and at elevated levels can induce apoptosis in vitro and in vivo [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…SAP is a pattern recognition protein that binds components of pathogens as well as apoptotic and autoimmune material [12,13]. SAP is involved in wound repair and the innate immune response [1416], and is a potent regulator of monocyte responses controlling fibrosis [1721]; however, SAP also potentially contributes to the pathogenesis of Alzheimer’s disease through the binding of amyloid plaques and neurofibrillary tangles (NFTs) [22–24]. SAP has been found to enter neurons, and at elevated levels can induce apoptosis in vitro and in vivo [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The pre-clinical data on administration of exogenous PTX-2 has shown significant benefit in models of several chronic fibrotic diseases, including bleomycin-or TGF-induced lung fibrosis, 12,40,41 ischaemia reperfusion injury, 7 corneal injury, 42 and radiation-induced oral mucositis and fibrosis. 43 Importantly, pre-clinical testing in models of chronic liver disease including CCl4-and bile duct ligation-induced liver fibrosis were similarly encouraging. 14 When these liver-injured mice were treated with recombinant PTX-2, fibrosis development was significantly inhibited, as was the activation of fibrogenic myofibroblasts, inflammatory cytokines (IL-1b, IL-6 and TNF-a), and pro-fibrogenic genes (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…As PTX‐2 is known to play an important role in the inhibition of hepatic stellate cell activation as well as in the regulation of fibrogenesis and wound healing, repletion with recombinant protein is a promising therapeutic target. The pre‐clinical data on administration of exogenous PTX‐2 has shown significant benefit in models of several chronic fibrotic diseases, including bleomycin‐ or TGF‐induced lung fibrosis, ischaemia reperfusion injury, corneal injury, and radiation‐induced oral mucositis and fibrosis . Importantly, pre‐clinical testing in models of chronic liver disease including CCl4‐ and bile duct ligation‐induced liver fibrosis were similarly encouraging .…”
Section: Discussionmentioning
confidence: 99%
“…This claim was supported by studies that demonstrated that suppression of reactive oxygen species with superoxide dismutase (Murphy et al , ) or the inhibition of cytokines favorably alters the disease course (Sonis, ). Mitigation of oral mucositis with serum amyloid P, a protein instrumental in curtailing disproportionate fibrotic response in damaged tissues, further strengthened the significance of submucosal tissue response in disease development (Murray et al , ).…”
Section: Discussionmentioning
confidence: 99%